Weekly carfilzomib and dexamethasone in Japanese patients with relapsed or refractory multiple myeloma: A phase 1 and PK/PD trial. Issue 10 (5th September 2018) - Maruyama, Dai; Tobinai, Kensei; Chou, Takaaki; Taniwaki, Masafumi; Shumiya, Yoshihisa; Iida, Shinsuke
Abstract : This open‐label multicenter phase 1 study evaluated the safety, tolerability, efficacy, pharmacokinetics and pharmacodynamics of weekly carfilzomib and dexamethasone (Cd) in Japanese patients with relapsed or refractory multiple myeloma (RRMM). Carfilzomib was administered by 30‐minute intravenous infusion on Days 1, 8 and 15 in a 28‐day cycle starting at 20 mg/m 2 on Day 1/Cycle 1 and 70 mg/m 2 thereafter until progressive disease or unacceptable toxicity. Dexamethasone 40 mg was administered on Days 1, 8, 15 and 22 in Cycles 1‐9 and on Days 1, 8 and 15 thereafter. Six patients were enrolled between March 2015 and June 2015. Patients had received a median of 4.5 (range, 4‐8) prior regimens; all patients had previous therapies with bortezomib and immunomodulatory drugs. Of the 6 patients, 1 had a dose‐limiting toxicity (DLT), and tolerability was confirmed. The DLT was grade 3 thrombotic microangiopathy, which was considered serious and occurred on Day 11/Cycle 1. All 6 patients (100%) experienced at least 1 grade ≥3 adverse event (AE). Two patients (33.3%) experienced AE (also considered adverse drug reactions) leading to study discontinuation: thrombotic microangiopathy (Day 11/Cycle 1) and thrombotic thrombocytopenic purpura (Day 6/Cycle 2). The overall response rate was 83.3% (95% confidence interval, 43.6‐97.0). The weekly Cd regimen at a carfilzomib dose of 20/70 mg/m 2 was well‐tolerated among Japanese patients with RRMM. Our results could be the basis for the further development of carfilzomib treatment considering safety profiles including microangiopathy‐related events and efficacy. Abstract : This open‐label, multicenter, phase 1 study is the first to assess the safety and efficacy of a weekly carfilzomib and dexamethasone (Cd) regimen with carfilzomib at a dose of 20/70 mg/m 2 by 30‐minute intravenous infusion and dexamethasone at a dose of 40 mg in Japanese patients with relapsed or refractory multiple myeloma (Figure 1 ). Among the 6 patients enrolled, 1 had a dose‐limiting toxicity (grade 3 thrombotic microangiopathy); all patients experienced at least 1 grade ≥3 adverse event; 2 patients (33.3%) experienced adverse drug reactions leading to study discontinuation (thrombotic microangiopathy [Day 11/Cycle 1] and thrombotic thrombocytopenic purpura [Day 6/Cycle 2]); the overall response rate (partial response or better) was 83.3% (95% confidence interval, 43.6%–97.0%); and the clinical benefit rate was also 83.3%. Our results could be the basis for further development of carfilzomib treatment considering safety profiles including microangiopathy‐related events and efficacy.